PMP project management professional : practice tests - Heldman, Kim; Mangano, Vanina (2021)
Boost your confidence through preparation before you take the new Project Management Professional (PMP) exam. The PMP Project Management Professional Practice Tests is the hands-on way to prepare for the exam and achieve your certification. Access : Three practice tests; ---Study questions that cover the three PMP performance domains; --Test your knowledge with three additional bonus exams; --Practice with a total of 1,000 unique test questions. The Project Management Professional (PMP) certification was developed by the Project Management Institute (PMI). The certification requires extensive project management experience, instructional hours, and successful completion of the certification exam. Well-known PMP authors and experts, Kim Heldman and Vanina Mangano, have written practice questions that will help you get ready for testing as you work toward certification. The test questions provide you with coverage within each of the performance domains: people, process, and business environments. Project managers play a critical role in today’s organizations. When you pass the exam and earn certification, you will gain additional recognition for your skill set and expertise. This confidence-building guide also connects you to an interactive online learning environment and test bank including all the practice exam questions. Get help reaching your professional goals with the right PMP tools! --
People (Domain 1.0) -- Process (Domain 2.0) -- Business Environment (Domain 3.0) -- Full-Length Practice Exam 1 -- Full-Length Practice Exam 2 -- Full-Length Practice Exam 3 -- Answers and Explanations.
"2021 exam update" -- Cover.
Includes index.
Keywords: Project management; Project management -- Examinations; Gestion de projet; Gestion de projet -- Examens; Project management; Project management -- Examinations